KAJIAN AWAL PEMBUATAN BETON POROUS UNTUK PAVING BLOCK RAMAH LINGKUNGAN - Yenni Ciawi; Made Alit Karyawan Salain; I Putu Adi Yana (Universitas Lambung Mangkurat, 2022)
In heavily populated urban areas, high rainfall can cause inundation and even flooding because the catchment area is decreasing. To reduce rainwater runoff and increase groundwater recharge, porous concrete can be used in housing area, in parking lots and roads with low traffic loads. Porous concrete is an environmentally friendly and sustainable building material. This study aims to examine the effect of aggregate composition on the porosity and tensile strength of porous concrete. The composition of the concrete mixture is determined based on the weight ratio between portland cement type I (PC) and coarse aggregate (AK), i.e. 1 PC : 3 AK, 1 PC : 4 AK, and 1 PC : 5 AK and the ratio of fine aggregate weight (AH) of 0 ; 0.5 ; 1, and the w/c is 0.5. For each variation, six 150 mm cubes were made. The parameters tested were slump, volume weight, porosity and compressive strength at day 28. The results show that the more coarse aggregate, the lower the volume weight and its compressive strength, and the higher the porosity and slump. Fine aggregate addition increases the compressive strength and volume weight and decrease slump value and porosity. The highest slump value (205 mm) and the smallest volume weight and compressive strength were obtained from concrete mixture with PC/AK=1/5 without AH content. The smallest slump (170 mm) and porosity values were obtained from concrete mixture with PC/AK=1:3 and AH/AK=1 and the largest volume weight and compressive strength. In this study, the slump value tends to be directly proportional to porosity and inversely proportional to volume weight and compressive strength. For further research, it is recommended that the w/c value be reduced to get a larger porosity value but without a significant decrease in compressive strength.